Total edge irregularity strength of octagonal grid graph - Siddiqui M.K.; Miller M.; Ryan J. (Utilitas Mathematica, 2017)
An edge irregular total k-labeling of a graph G = (V, E) is a labeling of vertices and edges such that the total edge-weights are different for all pairs of distinct edges, where total edge weight is the sum of the labels of vertices and the label of the edge between these two vertices. The minimum k for which the graph G has an edge irregular total k-labeling is called the total edge irregularity strength of G. In this paper, we determine the exact values of the total edge irregularity strength of octagonal grid graph.